2020
DOI: 10.1007/s13324-020-00392-1
|View full text |Cite
|
Sign up to set email alerts
|

Local regularity of axisymmetric solutions to the Navier–Stokes equations

Abstract: In the note, a new regularity condition for axisymmetric solutions to the non-stationary 3D Navier-Stokes equations is proven. It is slightly supercritical. Keywords Navier-Stokes equations, axisymmetric solutions, local regularityData availability statement Data sharing not applicable to this article as no datasets were generated or analysed during the current study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…One can show also that σ ∈ L ∞ (Q(R)) for any 0 < R < 1, see, for example, papers [19] and [17]. What actually has been proved in paper [18], see also the last section of the present paper, is as follows:…”
Section: (): V-volsupporting
confidence: 63%
See 2 more Smart Citations
“…One can show also that σ ∈ L ∞ (Q(R)) for any 0 < R < 1, see, for example, papers [19] and [17]. What actually has been proved in paper [18], see also the last section of the present paper, is as follows:…”
Section: (): V-volsupporting
confidence: 63%
“…With the regards to the state of arts in the regularity theory of axially symmetric solutions to the Navier-Stokes equations, we could refer to the previous papers [17] and [18] of the author and especially to references therein. For example, one could mention the following very interesting papers: [6], [23], [10], [14], [16], [2], [21], [4], [19], [8], [15], [9], [3], [22], and [25].…”
Section: (): V-volmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, as it has been done in [26] and [24], one can show that σ ∈ L ∞ (Q(R)) for any 0 < R < 1.…”
Section: Theorem 13 Let V Be An Axially Symmetric Solution To the Cau...mentioning
confidence: 55%
“…In this note, we continue to analyse potential singularities of axisymmetric solutions to the non-stationary Navier-Stokes equations. In the previous paper [24], it has been shown that an axially symmetric solution is smooth provided a certain scale-invariant energy quantity of the velocity field is bounded. By definition, a potential singularity with bounded scale-invariant energy quantities is called the Type I blowup.…”
Section: Introductionmentioning
confidence: 97%